Adult weight management patients' perceptions of family dynamics and weight status. Issue 5 (24th June 2019) - Pratt, Keeley J.; Ferriby, Megan; Brown, Callie L.; Noria, Sabrena; Needleman, Bradley; Skelton, Joseph A.
Summary: Our overall objective was to describe the parent‐child, romantic, and family dynamics of adult weight management program (WMP) patients, and associations with children's and partners' weight status. First, we determined if family functioning mediated the effect between parent‐child feeding practices and perceived child weight status, and romantic relationship anxiety and avoidance and perceived partner weight status. Second, we assessed if perceived child and partner weight status moderated the associations between family functioning and parent‐child feeding practices and romantic relationship anxiety and avoidance, respectively. Patients (N=203) who resided with a child and partner from two WMPs completed assessments of parent‐child feeding practices (Child Feeding Questionnaire), romantic relationship anxiety and avoidance (Relationship Structures Questionnaire), family functioning (Family Assessment Device General Functioning Scale), and perceived child and partner weight status. Bivariate analyses determined differences in weight status and relationship dynamics and family functioning, and mediation and moderation analyses were conducted to answer the two research questions. Family functioning was not a mediator between romantic relationship dynamics and partner weight status or parent‐child dynamics and child weight status. Lower family functioning was associated with higher parent‐child restrictive feeding practices, only among children with overweight/obesity. Similarly, lower family functioning was associated with higher anxiety and avoidance in romantic relationships, only for partners with overweight/obesity. Patients with children and/or partners with overweight/obesity reported more impaired family dynamics and functioning, compared to patients with children and/or partners with a healthy weight status.